Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Kolase di Raudhatul Athfal (RA) Al-Ikhlas Desa Siulak Kecil - Birrul Walid Primadasa (Journal on Education, 2024)
The development of fine motor skills in early childhood is essential, as it supports social adaptation and readiness for formal learning. This study explores efforts to improve children's fine motor skills through college activities at Raudhatul Athfal (RA) Al-Ikhlas in Siulak Kecil Village. The research uses a descriptive qualitative approach with primary data from direct observation of college activities and interviews with educators, and secondary data from relevant documents and archives. The findings reveal that the fine motor skills of children at RA Al-Ikhlas are relatively low, as evidenced by their difficulties in activities requiring eye-hand coordination and manual skills, such as cutting, buttoning, and holding pencils. Factors contributing to this deficiency include a lack of variety in learning media, limited teacher encouragement during activities, and infrequent play-based learning activities. The structured implementation of collage activities successfully enhanced children's fine motor skills by engaging in eye-hand coordination and manual skills, while also fostering their interest in interactive learning activities. Evaluation of these college activities provides educators with insights to improve teaching methods in the future, making the learning process more effective and optimal.